Does Female Empowerment Promote Economic Development? - Doepke, Matthias; Tertilt, Michele (2012)
Empirical evidence suggests that money in the hands of mothers (as opposed to their husbands) benefits children. Does this observation imply that targeting transfers to women is good economic policy? The authors develop a series of noncooperative family bargaining models to understand what kind of frictions can give rise to the observed empirical relationships. Then they assess the policy implications of these models. The authors find that targeting transfers to women can have unintended consequences and may fail to make children better off. Moreover, different forms of empowering women may lead to opposite results. More research is needed to distinguish between alternative theoretical models.